Development of an evidence-based complex intervention for community rehabilitation of patients with hip fracture using realist review, survey and focus groups. Issue 10 (11th October 2017) - Roberts, Jessica Louise; Din, Nafees Ud; Williams, Michelle; Hawkes, Claire A; Charles, Joanna M; Hoare, Zoe; Morrison, Val; Alexander, Swapna; Lemmey, Andrew; Sackley, Catherine; Logan, Phillipa; Wilkinson, Clare; et al.
Abstract : Objectives: To develop an evidence and theory-based complex intervention for improving outcomes in elderly patients following hip fracture. Design: Complex-intervention development (Medical Research Council (MRC) framework phase I) using realist literature review, surveys and focus groups of patients and rehabilitation teams. Setting: North Wales. Participants: Surveys of therapy managers (n=13), community and hospital-based physiotherapists (n=129) and occupational therapists (n=68) throughout the UK. Focus groups with patients (n=13), their carers (n=4) and members of the multidisciplinary rehabilitation teams in North Wales (n=13). Results: The realist review provided understanding of how rehabilitation interventions work in the real-world context and three programme theories were developed: improving patient engagement by tailoring the intervention to individual needs; reducing fear of falling and improving self-efficacy to exercise and perform activities of daily living; and coordination of rehabilitation delivery. The survey provided context about usual rehabilitation practice; focus groups provided data on the experience, acceptability and feasibility of rehabilitation interventions. An intervention to enhance usual rehabilitation was developed to target these theory areas comprising: a physical component consisting of six additional therapy sessions; and a psychological component consisting of a workbook to enhance self-efficacy and a patient-held goal-setting diary for self-monitoring. Conclusions: A realist approach may have advantages in the development of evidence-based interventions and can be used in conjunction with other established methods to contribute to the development of potentially more effective interventions. A rehabilitation intervention was developed which can be tested in a future randomised controlled trial (MRC framework phases II and III). Trial registration number: ISRCTN22464643, Pre-results.